A study on investment in CIMB unit trust in Kota Bharu / Wan Hazwani Wan Rukni - Wan Rukni, Wan Hazwani (2012)
This paper reports an exploratory study on relationship between unit trust agent professionalism, diversification of risk, liquidity of asset and dividend given towards investment in CIMB unit trust in Kelantan. The objective of this study is to determine relationship between Professionalism unit trust agent, diversification of risk, liquidity of asset and dividend given will be the most factor influence the investment in CIMB unit trust. For this study, the primary data are used and the researcher distribute for 100 questionnaires which is 100 respondents from the customer/investors in CIMB Kota Bharu. The data collected was tested by using the T-test hypotheses. Overall the researcher concluded that the two of four hypotheses of these variables are acceptable and reliable for forecasting. From the finding, it can be concluded that most of the respondents whose comes to this unit trust bank because, they concern about professionalism unit trust agent, diversification of risk, liquidity of asset and dividend given